ANALISIS PENGARUH E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI DALAM PENGAMBILAN KEPUTUSAN UNTUK BERWIRAUSAHA - Hakim, Firdaus Nurul; Syahfrudin Z, Achmad (STIE Atma Bhakti, 2020)
This study aims to empirically prove the hypotheses tested, namely: the effect of e-commerce on decision making for entrepreneurship, and the influence of accounting information systems on decision making for entrepreneurship. The object of the study was the Accounting Study Program Student Faculty of Economics, University of Muhammadiyah Jember Force 2016. In this study the method used in collecting data was a survey method by distributing questionnaires. The population in this study was the Accounting Study Program Student Faculty of Economics, University of Muhammadiyah Jember, 2016. The data collected and processed in this study included the type of primary data obtained from distributing questionnaires to 113 respondents taken as samples with a purposive sampling technique. Then the data obtained were analyzed using multiple linear regression models. The results of the calculation of the regression equation with the SPSS program in this study accept the first hypothesis, namely that knowledge about e-commerce has a significant and positive influence on decision making for entrepreneurship, and accepts the second hypothesis namely understanding of accounting information systems has a significant and positive influence on decision making for entrepreneurship. In this study an understanding of accounting information systems is more influential on decision making for entrepreneurship than e-commerce. This is because respondents have taken accounting information system courses for 1 semester. Whereas in e-commerce there are no special courses so students better understand the accounting information system.